Desain Microgrid untuk Militer - Putri, Dianing Novita Nurmala; Sari, Tyas Kartika; Irianto, Chairul G; Widjaja, Maula Sukma (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
With more than 300,000 members, Indonesia's military forces, consisting of the army, navy and air force, have a large need for electricity. A reliable and safe electricity source is a must. Especially in carrying out the task of defending the country in conditions that are critical and threaten the security of the country. For this reason, the use of microgrids can be a solution for energy independence. In addition, using microgrids consisting of renewable energy sources helps the government increase the renewable energy share. This research discusses the design and application of microgrids in the military. The study case is done in one of military facility in Indonesia. The first step is to identify the type of the system if it is on grid or off grid, then calculate the load, source of energy and decide the control system. In this study case where the load is 3082 kWh/day, it require 860pcs PV of 320Wp capacity with cycle charging controller systems and Diesel Generator with capacity of 260kW. It is hoped that it can be a guide for the military in Indonesia in implementing microgrids.